Evaluasi Rambu dan Marka Pada Kota Serang Ruas Jalan Veteran - Jalan Jendral Ahmad Yani: Evaluation of Signs and Markings in The Road Segment of Veteran - General Ahmad Yani Street in Serang City - Bethary, Rindu; Budiman, Arief; Hibatullah , Aziz (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
One of the vital key collector roads in Serang City is Jl. Veteran - Jl. General Ahmad. This road serves an important purpose because it is one of the key routes in Banten Province. However, traffic congestion and accidents are common on this road. The purpose of this study was to determine the number of traffic signs and road markings on Jl. Veteran - Jl. General Ahmad Yani and whether they are in accordance with PERMENHUB No. 13 of 2014 and No. 67 of 2018, as well as to determine the location of the Directional Signs (RPPJ) and whether they are in accordance with the stopping sight distance analysis (JPH) according to PERMENHUB No. 13 of 2014. The analysis of the suitability of signs from 78 signs and 24 road markings on Jl. Veteran - Jl. General Ahmad Yani revealed that 23 signs (29.49%) did not comply with PERMENHUB regulations No.13 of 2014, and 11 road markings (45.83%) did not comply with PERMENHUB regulations No.67 of 2018. The result of this study also revealed that 3 signs (50.00%) of the 6 observed signs fulfilled the stopping sight distance analysis on Jl. Veteran - Jl. General Ahmad Yani and the reverse direction.